Hydration status of female basketball players before and during training - Mertens, E.; Aerenhouts, D.; Deforche, B.; Clarys, P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Data on hydration status of female basketball players and basketball performance are scarce. Dehydration has negative consequences on health and sports performance. In this study we assessed the hydration status of female basketball players. The aim of the present study was to evaluate the pre-training hydration status and to study the influence of the pre-training hydration status on training intensity. Methods: All 20 female basketball players (age 18,2 ± 3,8, height 167,8 ± 6,4) of a local competitive basketball club participated in this study. Urine specific gravity (PAL-10S refractometer) as an indicator of hydration status was measured before training. Body mass was measured before and after the training session in combination with fluid intake (assessed by weighing a personalized bottle of water before and after training) was used to calculate sweat loss. During training all players had to wear a SenseWear Armband, sampling at the highest rate (1/s), to estimate number of steps and total intensity. Results: Pre-training urine specific gravity ranged from 1.004 to 1.027 g/ml. Eight out of 20 players started training dehydrated. The mean (± SD) sweat loss during training amounted to 655,4 ± 249,7 ml/h, and mean fluid intake was 446,9 ± 168,6 ml/h. There was a significant correlation between sweat loss and number of steps (6121,9 ± 610,1) during training (r=0.577, p=0.008), but no correlation between sweat loss and intensity (r=0.114, p=0.632). There was no significant difference between pre-training well hydrated and pre-training dehydrated players in number of steps (p=0.499) and intensity (p=0.631). Discussion: It can be concluded the 40% of the players started the training dehydrated. The hydration status was not related with training intensity, as measured by number of steps and intensity.